Evaluating bioavailability of organic pollutants in soils by sequential ultrasonic extraction procedure - Wu, Xiang; Zhu, Lizhong (Chemosphere (Oxford), 2016)
Under current retrospective risk assessment framework, the total concentrations of organic pollutants in soils have been employed as the standard for over 30 years. The total concentrations reflect the overall accumulation in soils but tend to be overly conservative for assessing the ecological risks, where the bioavailability plays an important role. In this study, the bioavailability of organic pollutants in soils was evaluated using a stepwise and tiered classification method, namely the sequential ultrasonic extraction procedure (SEUP). The water-soluble and acid-soluble fractions extracted by the SEUP were the bioavailable fractions. The reliability and environmental relevance of the speciation method were examined with representative organic pollutants using the root uptake methods and the semipermeable membrane devices (SPMDs). The plant uptake amounts corrected with weight were highly correlated with the bioavailable fractions (R2 > 0.75). The amounts of the bioavailable fractions were negatively correlated with the logKow values (R2 ranging from 0.71 to 0.77) of the organic pollutants and the contents of soil organic matter (R2 ranging from 0.68 to 0.96). As a refinement of the current risk assessment framework, the SUEP that has proved to be a reliable and convenient is thus highly recommended for evaluating the bioavailability of organic pollutants in soils. [Display omitted] •SUEP is used to evaluate bioavailability of organic pollutants in soils.•Bioavailable fraction includes water and acid-soluble fractions.•Bioavailable fraction is negatively correlated with logKow and SOM.•Amount of plant uptake is highly correlated with bioavailable fraction.